Genetic Overlap Between Attention Deficit/Hyperactivity Disorder and Autism Spectrum Disorder in SHANK2 Gene - Ma, Suk-Ling; Chen, Lu Hua; Lee, Chi-Chiu; Lai, Kelly Y. C.; Hung, Se-Fong; Tang, Chun-Pan; Ho, Ting-Pong; Shea, Caroline; Mo, Flora; Mak, Timothy S. H.; Sham, Pak-Chung; Leung, Patrick W. L. (Frontiers in Neuroscience, 2021)
Background: Recent findings indicated a high comorbidity between attention-deficit/hyperactivity disorder (ADHD) and autism spectrum disorder (ASD), as well as shared genetic influences on them. The latter might contribute at least partly to the former clinical scenario. This study aimed at investigating whether SHANK genes were potential pleiotropic genes to the two said disorders, underlying their genetic overlap. Methods: This study recruited 298 boys with ADHD (including 256 family trios of one ADHD boy and his two biological parents), 134 boys with ASD, 109 boys with both ADHD and ASD, and 232 typically developing boys as community controls. They were aged between 6 to 11 years old. Results: There was no significant difference in allele frequency of a number of single nucleotide polymorphisms (SNPs) in SHANK2/SHANK3 between the three clinical groups (ADHD, ASD and ADHD+ASD) and between the two control groups (community controls and pseudo-controls) respectively. The three clinical groups and the two control groups were thus respectively combined. A comparison between the two aggregated samples identified significant evidence of disease association for three SHANK2 SNPs with both ADHD and ASD, even after multiple testing correction: rs11236616 (OR=0.762, permuted p=0.0376), rs7106631 (OR=0.720, permuted p=0.0034) and rs9888288 (OR=0.770, permuted p=0.0407). Comparisons among individual groups pointed to a similar trend of findings. Conclusion: SHANK2 could be considered a potential pleiotropic gene underlying the genetic overlap between ADHD and ASD. This might contribute partly to their high comorbidity in the afflicted children.